Framework for optimization of long-term, multi-period investment planning of integrated urban energy systems. (15th June 2021) - van Beuzekom, Iris; Hodge, Bri-Mathias; Slootweg, Han
Abstract: In order to achieve stringent greenhouse gas emission reductions, a transition of our entire energy system from fossil to renewable resources needs to be designed. Such an energy transition brings two main challenges: most renewables generate variable electric energy, yet most demand is currently not electric ( carrier mismatch ) and does not always manifest at the same time as supply ( temporal mismatch ). Integrating multiple energy infrastructures can address both challenges by using the synergy between different energy carriers; building on existing infrastructure, while allowing a robust and flexible integration of the new. This paper proposes an optimization framework for long-term, multi-period investment planning of urban energy systems in an integrated manner. We formulate it as a mixed-integer linear program, combining a capacitated facility location with a multi-dimensional, capacitated network design problem. It includes generation and network expansion planning as well as interconnections between networks and storage infrastructure for each energy system. It can incorporate pathway effects like techno-economic developments, policy measures, and weather variations. The intended use is to support urban decision makers with long-term investment planning, though it can be tailored to fit other geographical or temporal scales. We demonstrate the model using two cases based on an average city in The Netherlands, which wants to reduce its CO2 -emissions with 95% by 2050. In the first case, we include explicit carbon-emission constraints to study the effects of the carrier mismatch. In the second case, we implement interannual weather variations to analyze the temporal mismatch. The results give valuable insights into the energy transition design strategy for urban decision makers. They also show the future potential, as well as the computational challenges of the optimization framework. Graphical abstract: Highlights: Generic optimization framework for energy transition design of urban infrastructures. Full coupling of multiple energy infrastructures provides serious potential for robust and flexible solutions. Multi-period investment planning allows explicit inclusion of social, techno-economical, and physical pathway effects. Strict climate goals can be achieved and interannual weather variations balanced well. Novel formulation of a capacitated facility location network design problem implies significant mathematical and computational complexity.